Topiramato oral en estatus epiléptico refractario. Revisión bibliográfica y experiencia local - Mena U., Boris; Aguilera O., Ledda; Gómez R., Rodrigo; González R., Pablo (Revista Hospital Clínico Universidad de Chile, 2009)
Aim. To assess the efficiency of topiramate (TPM), an antiepileptic medication which possesses multiple mechanisms of action, a wide therapeutic spectrum and good pharmacokinetics in the management of status epilepticus (SE), especially in refractory. Several reports have shown that TPM presents different efficacy in the management of different types of refractory status epilepticus, both adults and children. Also present our experience with two patients with SE who responded early without TPM oral complications. Conclusions. TPM oral as drug associated, is an antiepileptic medication that has shown therapeutic efficacy in cases reports and observational studies the management SE of different types and nature. This efficacy has not been contrasted with randomized controlled trials and prospective studies, therefore, future studies with larger numbers of patients are needed to confirm published reports.